A first look at the SMACS0723 JWST ERO: spectroscopic redshifts, stellar masses, and star-formation histories. Issue 1 (28th November 2022) - Carnall, A C; Begley, R; McLeod, D J; Hamadouche, M L; Donnan, C T; McLure, R J; Dunlop, J S; Milvang-Jensen, B; Bondestam, C L; Cullen, F; Jewell, S M; Pollock, C L
ABSTRACT: We present a first-look analysis of the JWST ERO data in the SMACS J0723.3-7327 cluster field. We begin by reporting 10 new spectroscopic redshifts from λobs = 1.8–5.2 μm NIRSpec medium-resolution ( R = λ/Δλ = 1000) data. These are determined via multiple high-SNR emission line detections with five objects at 1 < z < 3 displaying multiple rest-frame near-infrared Hydrogen Paschen lines, and five objects at 5 < z < 9 displaying rest-frame optical Oxygen and Hydrogen Balmer lines. For the five higher-redshift galaxies we extract fluxes in six NIRCam bands spanning λobs = 0.8–5 μm and perform spectral energy distribution fitting in combination with existing HST photometry. The 7 < z < 9 objects exhibit a U-shaped pattern across the F 277 W, F 356 W, and F 444 W bands, indicating a Balmer break seen in emission (Balmer jump) and high-equivalent-width [O iii ] emission. This indicates an extremely young stellar population with the bulk of the current mass having formed within the past 10 Myr. We report robust stellar masses and mean stellar ages from our spectral fitting with the four z > 6 galaxies exhibiting low-stellar masses from log10 ( M * /M⊙ ) = 7.1–8.2, and correspondingly young mean stellar ages of only a few Myr. This work highlights the critical importance of combining large upcoming NIRCam surveys with NIRSpec follow-up to measure the spectroscopic redshifts necessary to robustly constrain physical parameters.